Paired-associate learning, phoneme awareness, and learning to read. - Hulme, C; Goetz, K; Gooch, D; Adams, J; Snowling, M (2007)
We report two studies examining the relations among three paired-associate learning (PAL) tasks (visual-visual, verbal-verbal, and visual-verbal), phoneme deletion, and single-word and nonword reading ability. Correlations between the PAL tasks and reading were strongest for the visual-verbal task. Path analyses showed that both phoneme deletion and visual-verbal PAL were unique predictors of a composite measure of single-word reading and of irregular word reading. However, for nonword reading, phoneme deletion was the only unique predictor (and visual-verbal PAL was not a significant predictor). These results are consistent with the view that learning visual (orthography) to phonological mappings is an important skill for developing word recognition skills in reading and that individual differences in this ability can be tapped experimentally by a PAL task.